ASHLEIGH SAYERâS METHOD OF COMMUNICATIVE LANGUAGE TEACHING IN PSYCHOLINGUISTICS CLASS TO SIXTH SEMESTER ENGLISH DEPARTMENT STUDENTS AT IAIN ANTASARI BANJARMASIN ACADEMIC YEAR 2009/2010 - Subhan, Abdu (English Department of Faculty of Tarbiyah and Teachers Training, 2012)
ABSTRACTThis study describes Ashleigh Sayerâs method of communicative language teaching in psycholinguistics class to sixth semester English Department students at IAIN Antasari Banjarmasin academic year 2009/2010. The result of the research denoted that Ashleigh Sayer used communicative language teaching method and applied some techniques which are adopted from communicative method it self. Some techniques that Ashleigh Sayer used in her class including: pair-work, group-work, learning by teaching, writing logs, English communication, informal greeting, showing agenda, independent participant, circle setting, authentic material, media, ignoring errors of grammar, reading activity and questions and answers. The response of the students regarding her method and techniques is classified into high category. It is based on the numbers of students who like her method and techniques very much is 43 students, 14 students who quite like, 5 students less like and no student dislike her class. It can be concluded so because when Ashleigh Sayer was teaching in her psycholinguistics class to the students, she teaches in a very good way which the approach is communicative approach. Communicative method lets the students practice more their language and the teacher always makes the students able to enjoy and less shy in the class which will help the teacher to teach all the material.